PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN WILAYAH DATARAN RENDAH DI DESA CIPOCOK SERANG BANTEN - Alfina Rahma Putri; Keyla Atala Avanza Satiri; Rafa Aliyah Shabira (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the forms of community participation in the development of lowland areas, focusing on contributions in the form of ideas, labor, and material support. The approach used is qualitative through a literature study, examining various scholarly documents and case studies, particularly related to the development of Cipocok Village, Serang, Banten. The results indicate that community participation tends to be high when residents are actively invited by the organizers, especially in terms of contributing ideas and labor. However, participation in the form of material support remains low due to economic limitations. The driving factors for participation include responsive local leadership, the presence of active youth organizations, direct economic benefits, and open communication strategies. On the other hand, obstacles include a culture of modesty, dependence on organizers, and a low level of collective awareness about the importance of citizens' roles in development. Tourism attractions developed based on local culture and daily activities have proven to be effective tools for empowering the community. The involvement of youth in managing these attractions serves as a key driver for the sustainability of rural development. This study recommends participatory facilitation and continuous training to strengthen the community's role in regional development.